Aperture elongation of the femoral tunnel on the lateral cortex in anatomical double-bundle anterior cruciate ligament reconstruction using the outside-in technique. Issue 38 (18th September 2020) - Akaoka, Yusuke; Tensho, Keiji; Shimodaira, Hiroki; Koyama, Suguru; Iwaasa, Tomoya; Horiuchi, Hiroshi; Saito, Naoto
Abstract : Abstract: In anatomical anterior cruciate ligament reconstruction surgery using the outside-in technique, the aperture of the femoral lateral cortex may become elliptical. Retrospective cross-sectional study To evaluate the extent of elliptical eccentricity in lateral apertures relative to aperture positioning and clinical failure rate in anatomical anterior cruciate ligament double-bundle reconstruction using outside-in technique. In 75 patients, the aperture elongation factor was defined as the ratio of the major axis of the elliptical aperture to the drill size. Using the lateral epicondyle as a reference point, the lateral femur was divided into sections by distance and angle, and the minimum area was evaluated to assess the relationship between the elongation factor and aperture position of the lateral cortex for each bundle. The incidence and associated clinical performance regarding cortical button migration were also investigated. Aperture elongation factors were 120.2 ± 13.3% and 120.0 ± 16.3% on the anteromedial (AM) and posterolateral (PL) sides, respectively. Femoral tunnel elongation was smallest when the entry point axis were both between 30 to 60° and distance was between 10 to 20 mm and 0 to 10 mm on the AM and PL sides, respectively. During the postoperative follow-up period, intra-tunnel migration was confirmed in 4 of 75 cases (5.3%). Fixation failure neither affected clinical scores nor knee laxity. Areas of minimum elongation for each bundle on both AM and PL sides were found anteroproximally to the lateral epicondyle and positioned near each other. Elongation did not directly affect the clinical outcome. Level of evidence grade: prognostic level III